Chronostratigraphy of talus flatirons and piedmont alluvium along the Book Cliffs, Utah – Testing models of dryland escarpment evolution. (15th December 2021) - McCarroll, Nicholas R.; Pederson, Joel L.; Hidy, Alan J.; Rittenour, Tammy M.
Abstract: Research on the evolution of dryland escarpments and what drives and controls their erosional retreat have been limited by a lack of chronologically constrained records. Prior investigations of escarpments in the southwestern U.S. and globally garner two endmember conceptual models – one focused on bottom-up baselevel drivers and autogenic variations in piedmont and toeslope erosion processes, the other focused on the role of climate as a top-down forcing mechanism on sediment production and transport from cliffs. We test these conceptual models along a section of the Book Cliffs in central Utah, where climate has varied strongly and baselevel has fallen significantly over the late Quaternary. Four generations of talus flatirons and piedmont terraces are preserved in the study area we date them by optically stimulated luminescence and 10 Be-exposure techniques. OSL depositional ages cluster into four generations of deposits with mean ages and mean standard errors of 117.8 ± 6.7 ka, 83.4 ± 3.3 ka, 52.4 ± 1.8 ka, and 5.6 ± 0.3 ka. 10 Be-exposure results from talus boulders protruding from flatirons confirm that the youngest generation of talus is Holocene, with recent rock-fall boulders still being received on the landform top. Older flatiron generations produce incoherent, minimum exposure ages reflecting an increasing dominance of in situ boulder weathering and a steady-state denudation rate of ∼45 mm/ky after tens of thousands of years. Based on the chronostratgraphy and correlation of talus and piedmont deposits, we interpret climate as the primary control on escarpment evolution. Depositional ages do not correspond to glacial epochs as historically presumed, but instead to episodes of intermediate and unstable or variable Pleistocene climate during Marine Isotope Stage-3 and 5 a/b. Results support the significance of high climate variability at millennial timescales in driving both sediment production by mass wasting from the cliff as well as sediment storage and reworking along the piedmont. In contrast, wetter climates of glacial epochs apparently caused greater erosion and sediment transport to trunk drainages. Our chronology also reveals a systematic decrease in deposit age with increasing distance up the piedmont from the regional baselevel of the Price River, consistent with transient fluvial incision and terrace abandonment. The Book Cliffs record notably does not correlate with similarly constrained records in Spain or the contrasting record from the Negev, yet they all share the feature of enhanced talus deposition and cliff retreat corresponding to climate instability rather than in response to steady glacial-climate conditions. Thus, we outline a model of escarpment evolution and retreat governed largely by top-down climate-forcing of sediment production and transport during climate variability, with local changes in baselevel and erosional processes on the piedmont being a modifying, secondary factor. Highlights: The Book Cliffs are an archetypal dryland escarpment where four generations of talus flatirons and piedmont alluvial terraces are preserved. Deposits cluster in age over the late Quaternary, correlating to times of intermediate climate with high millennial-timescale variability. Weathering of sandstone talus boulders occurs at a steady-state rate of ∼45 mm/ky, making exposure-ages erroneously young. Depositional ages are younger with increasing distance from baselevel, consistent with transient incision and terrace abandonment. Results support a model of cliff retreat controlled by climate, with erosion across the piedmont secondarily influenced by baselevel.